Development of Anthropometrics Database for Ages 19-21 in West Nusa Tenggara: Optimizing Secondary Data for Industrial Product Design - Fikrihadi Kurnia; Maharsa Pradityatama; Akbar Tawaqqal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to develop an anthropometric database for individuals aged 19-21 in West Nusa Tenggara (NTB) Province to support ergonomic product design tailored to local physiological needs. A descriptive quantitative approach was employed, involving direct measurements of body dimensions in a sitting posture from 52 samples selected via purposive sampling. Key measurements included sitting height, eye level while seated, shoulder height, popliteal length, and other relevant dimensions, analyzed for normality, sufficiency, and consistency. The data followed a normal distribution with sufficient sample validity. Percentile values (P1, P5, P50, P95, P99) revealed significant variations in body dimensions, providing a robust reference for ergonomic design across sectors like creative industries, education, healthcare, and agriculture. The anthropometric database enables designing inclusive, comfortable, and safe products that accommodate various body sizes, enhancing user experience and efficiency in NTB’s key industries. The study is limited to NTB’s 19-21 age group and seated posture measurements, restricting its applicability to Indonesia’s broader population or other postures. Future research should expand geographic scope and include diverse postures to enrich national anthropometric data. Keywords: Anthropometry, Ergonomic Design, Seated Posture, Percentiles, West Nusa Tenggara.